Developing English Micro Habits to Support English Language Acquisition in a Pesantren-Based Elementary School MI Unggulan Mambaus Sholihin Blitar - Zuraida Zuraida; Intan Susana; Dyah Ayu Soffiya Zein (Indonesian Journal Publisher, 2026)
English is not just a language for international communication, but a key tool that connects people, knowledge and opportunities in our interconnected world. Many Indonesians, including students in early education stage, are now faced with the need to master English language for the demands of the realization of Golden Indonesia 2045. Elementary school age is considered a critical period for acquiring a second or foreign language. Framed within a descriptive qualitative method, this research investigated how small but consistent English language practices are developed in students’ daily routine recognized with their unique religious and cultural environment in a pesantren setting to enhance their English proficiency. The data of the study were collected through certain ways including classroom instructions observations, in-depth interviews with the teachers, and documentation of the students learning activities. The analysis focused on describing the implementation strategies and contextual factors that influence the success of micro habit development in an Islamic elementary boarding school. Findings indicates that micro habits-such as greetings, classroom instruction, simple conversations, vocabulary repetition- within a pesantren based elementary school contributes to students’ engagement, vocabulary acquisition, students’ motivation and confidence in using English in simple but authentic context. The integration of pesantren culture and discipline embedded in students’ daily routine also donates valuable implication in promoting early English language acquisition. This research highlights the significant role of fostering micro habits in the development of language proficiency, emphasizing how such habits can serve as a crucial educational strategy for bridging the existing gaps in students' language skills. By integrating these small, consistent practices into their routines, educators can enhance the language acquisition process, ultimately improving the overall language skills of young learners, especially in culturally diverse environments like those found in pesantren schools.